2020
DOI: 10.1080/09168451.2020.1731299
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic acid, α-linolenic acid, and monolinolenins as antibacterial substances in the heat-processed soybean fermented withRhizopus oligosporus

Abstract: Antibacterial activities against Staphylococcus aureus and Bacillus subtilis were found in an ethanol fraction of tempe, an Indonesian fermented soybean produced using Rhizopus oligosporus. The ethanol fraction contained free fatty acids, monoglycerides, and fatty acid ethyl esters. Among these substances, linoleic acid and α-linolenic acid exhibited antibacterial activities against S. aureus and B. subtilis, whereas 1-monolinolenin and 2-monolinolenin exhibited antibacterial activity against B. subtilis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 21 publications
0
26
0
1
Order By: Relevance
“…ALA exhibited a significant antibacterial effect on Bacillus subtilis (MIC = 8 μg/ml), but not on Staphylococcus aureus (MIC = 600 μg/ml) (Kusumah et al, 2020). Moreover, ALA could inhibit the activity of the Mycobacterium tuberculosis shikimate kinase enzyme (IC 50 = 3.7 μg/ml) (Masoko, Mabusa, & Howard, 2016).…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…ALA exhibited a significant antibacterial effect on Bacillus subtilis (MIC = 8 μg/ml), but not on Staphylococcus aureus (MIC = 600 μg/ml) (Kusumah et al, 2020). Moreover, ALA could inhibit the activity of the Mycobacterium tuberculosis shikimate kinase enzyme (IC 50 = 3.7 μg/ml) (Masoko, Mabusa, & Howard, 2016).…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…In many preceding studies, ethyl linoleate, a naturally occurring fatty acid ester, was consistently reported with wide bioactive potential, e. g. anti‐inflammatory, [21,22] antibacterial, [23] anti‐acne, [24] and melanogenesis‐inhibitory properties [25] . Although less well‐known, α ‐linolenic acid was still evidenced for its bactericidal activities against Streptococcus aureus , Bacillus subtilis , [26] and pretentive agents against the risk of cardiovascular diseases [27] . Therefore, by containing a variety of bioactive components, Distichochlamy citrea n ‐hexane extract holds an significant potentiality as an important medicinal herb, potentially developed into therapeutic products.…”
Section: Resultsmentioning
confidence: 99%
“…In many preceding studies, ethyl linoleate, a naturally occurring fatty acid ester, was consistently reported with wide bioactive potential, e. g. anti-inflammatory, [21,22] antibacterial, [23] antiacne, [24] and melanogenesis-inhibitory properties. [25] Although less well-known, α-linolenic acid was still evidenced for its bactericidal activities against Streptococcus aureus, Bacillus subtilis, [26] and pretentive agents against the risk of cardiovas-…”
Section: Chemistryselectmentioning
confidence: 99%
“…Considering the lipophilic component variety of Bingöl propolis, it was quite remarkable that it was rich in unsaturated fatty acids such as oleic acid (omega 9), which provides significant benefits to human health in the daily diet, especially in EHI and EEI isolates. These unsaturated fatty acids, such as oleic acid, linoleic acid, and linolenic acid have been reported to show broadspectrum biological activity [35][36][37] . In addition, the many beneficial effects of α-amyrone and β-amyrin and sesquiterpenoids, which are dominant in EI isolate, have also been reported [38][39][40].…”
Section: Lipophilic Compoundsmentioning
confidence: 99%